INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM ETIKA BERMEDIA SOSIAL MAHASISWA GENERASI Z - Zulfikar, Zulfikar,; Muhammad Ramadhan; Muhammad; Rizaki Akbar (STAI Nusantara Kota Banda Aceh, 2026)
The rapid development of social media has significantly transformed the interaction patterns of Generation Z, particularly among university students, from conventional social spaces into open and dynamic digital environments. However, this transformation is not always accompanied by ethical maturity in communication, as evidenced by the widespread dissemination of unverified information, the use of inappropriate language, and the tendency toward impulsive communication on social media platforms. This condition indicates a gap between technological proficiency and the internalization of religious values. This study aims to analyze the internalization of Islamic Religious Education values in shaping the social media ethics of Generation Z students in the Islamic Religious Education Study Program, Faculty of Islamic Studies, Universitas Islam Kebangsaan Indonesia Bireuen. The study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that students possess an adequate understanding of Islamic ethical values, such as honesty, responsibility, politeness, and the principle of tabayyun (verification). However, the implementation of these values in social media practices remains inconsistent. This gap is influenced by the weak internalization of values and the strong pressures of the digital environment, which emphasize speed and popularity. Therefore, it is necessary to strengthen Islamic Religious Education through more contextual and practical approaches to foster deeper value internalization, thereby promoting ethical, reflective, and responsible behavior in social media use.